Affixation Process in Sundanese - Bram Denafri; Mery Melati; Sabri Koebanu (JURNAL ARBITRER, 2019)
This article focuses on the form of the affixation process in Sundanese. This study uses a qualitative approach. The data in this study are Sundanese sentences that contain affixation. The data sources in this study are (1) Sundanese dictionaries and (2) Sundanese speakers. The researcher collects data directly involved and is not directly involved in conversations with speakers of Sundanese. Furthermore, researchers also use note-taking techniques. Data analysis using the segmenting immediate constituent technique. Prefix in Sundanese consists of several types, including meN-~{n-}~{ny-}~{m-}~{ng}, pa-, pi-, pang-, sa-, si-,Â  ti-, di-, ka-, ba-, and per-. Infix in Sundanese includes -ar-, -al-, -um-, and -in-. Sufix in Sundanese, several types of suffixes including -an, -eun, -na, -keun, -ing, and -ning. Confix in Sundanese includes ka - an, pa - an, pang - na, pang-keun, pi - eun, pika - eun, sa - eun, sa - na, - keun, and n - keun.